A rare cause of hyperprolactinemia: persistent trigeminal artery with stalk-section effect - BALTACIOĞLU, FEYYAZ (SPRINGER-VERLAG, 2001)
The primitive trigeminal, otic, hypoglossal, and proatlantal intersegmental arteries are fetal anastomoses between the carotid and vertebrobasilar systems, Persistent trigeminal artery (PTA) is the most frequent embryonic communication between the vertebrobasilar and carotid systems in adults. We report a case of PTA compressing the left side of the pituitary gland and stark, in a patient with elevated blood prolactin level.
Keywords: persistent trigeminal artery; MRI; angiography; hyperprolactinemia